Thinking or acting: physical aggression in a therapeutic community: how best to manage it?. Issue 2 (3rd June 2014) - Ghazirad, Marjan; Newrith, Christopher
Abstract : Purpose: – The purpose of this paper is to provide an overview of a rare phenomenon of physical aggression in a Therapeutic Community (TC) and the clinical results of its management. Design/methodology/approach: – The case vignette illustrates the psychodynamic and socio-therapy elements of the treatment model worked within the service prior to, during and after the incident. The information demonstrates how the TC model finds significant value in the living-learning experience that is possible in physical aggression and its management. Findings: – The dynamic administration at the interface between TC with preparation groups has a potential pitfall which might increases the risk of aggression in TC. Originality/value: – It is an original study focusing on the interface between new notion of preparation groups and TC following a case of Physical aggression. Physical aggression is a rare incident in TCs and there are very limited literature about it. The paper has a distinctive feature of being prepared in collaboration with TC service users.